2010
DOI: 10.4149/neo_2010_01_001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well−being in advanced NSCLC patients in Serbia: impact of sociodemographic and clinical factors

Abstract: lung cancer, anxiety, depression, quality of life, chemotherapy, chemotherapy-induced nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Our study results suggest that a case management programme should involve assessment of a patient's physical condition and underlying disease is essential before treatment. The current study also indicated that refusing treatment was influenced by a patient, their families, or friend's experience of negative treatment effects and worry about the side effects of treatment, which is consistent with the results of previous study that identified psychosocial factors as a significant element in compliance with treatment (Ayres et al., ; Mahendran et al., ; Maric et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study results suggest that a case management programme should involve assessment of a patient's physical condition and underlying disease is essential before treatment. The current study also indicated that refusing treatment was influenced by a patient, their families, or friend's experience of negative treatment effects and worry about the side effects of treatment, which is consistent with the results of previous study that identified psychosocial factors as a significant element in compliance with treatment (Ayres et al., ; Mahendran et al., ; Maric et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Psychosocial factors have a significant impact on cancer patients' attitudes towards compliance with treatment, thereby causing refusal or discontinuation of treatment. These psychosocial factors included anxiety (Greer, Pirl, Park, Lynch, & Temel, 2008;Maric et al, 2010), depression, poor emotional and mental functioning (Maric et al, 2010), guilt and hostility (Ayres et al, 1994). A previous study revealed that distress and psychosocial needs (worry, fear, nervousness and sadness) are high in cancer patients at early stage, prior to chemotherapy (Mahendran, Lim, Chua, Lim, & Kua, 2015).…”
Section: Discontinuing Treatment and Related Factorsmentioning
confidence: 99%
“…The evidence on the relationship between SED and psychological wellbeing is conflicting and was described across 6 of the included studies [ 50 , 56 , 64 , 67 , 68 , 74 ]. While one study found that financial difficulty was associated with lower functional, emotional and spiritual wellbeing [ 74 ] another found that unemployed patients with cancer had less anxiety and depression [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Los estudios incluso reportan que algunos pacientes presentan depresión después de un tratamiento curativo, en este caso la resección quirúrgica pero es menor que en el preoperatorio (19,20) . En el estudio de Marc et al refieren que pacientes con bajas puntuaciones en estado funcional presentan mayor sintomatología ansiosa y depresiva (21) . En los pacientes con cáncer de pulmón, la literatura científica postula que ansiedad moderada a severa está presente en el 10-45% de los pacientes (9,18,22,23) .…”
Section: Introductionunclassified